Quantum Computing and Its Impact on Cloud Security: Opportunities and Threats (International Journal of Engineering and Computer Science, 2017)
Quantum computing is emerging as a transformative technology with the potential to revolutionize various industries, including cloud security. This paper explores the impact of quantum computing on cloud security, analyzing both the opportunities it presents and the threats it poses. While quantum computing introduces new security paradigms such as Quantum Key Distribution (QKD) and Post-Quantum Cryptography (PQC), it simultaneously threatens traditional cryptographic standards, including RSA and ECC encryption, which form the foundation of modern cloud security frameworks.The paper discusses the fundamental principles of quantum computing, comparing it with classical computing to highlight the key differences in processing power, encryption capabilities, and computational efficiency. It then delves into how quantum technologies can enhance cloud security through quantum-resistant encryption techniques and improved threat detection models. However, the emergence of quantum computing also introduces significant risks, particularly its ability to break widely used encryption methods, leading to potential data breaches and security vulnerabilities in cloud infrastructures.A comprehensive literature review is included, summarizing existing research on quantum cryptographic methods, potential vulnerabilities, and countermeasures being developed by organizations such as NIST (National Institute of Standards and Technology) and leading tech companies like IBM and Google. The review highlights the urgency of transitioning toward quantum-resistant security protocols before large-scale quantum computers become practical.Furthermore, the paper provides a detailed analysis of countermeasures, including post-quantum encryption algorithms, hybrid encryption models, and the implementation of quantum-secure cloud infrastructures. The research is supplemented with tables and graphical representations, illustrating the projected growth of quantum cryptographic adoption and the estimated timeline for quantum threats to materialize.While quantum computing presents significant opportunities for strengthening cloud security, it also poses existential threats to existing encryption standards. Organizations must proactively invest in quantum-safe technologies and implement security frameworks that can withstand the quantum era. This paper serves as a critical resource for cloud service providers (CSPs), cybersecurity professionals, and policymakers seeking to understand and mitigate the implications of quantum computing on cloud security.